Corporate equality index 2015 (Washington, DC Human Rights Campaign Foundation, 2015)
Rating American workplaces on gay, lesbian, bisexual, and transgender equality.
UCWS-3158g, UCWS-3159g donated by Thomson Reuters - May 2016
Keywords: Gays -- Employment -- United States; Lesbians -- Employment -- United States; Corporations -- United States -- Directories